2016
DOI: 10.18203/issn.2455-4510.intjresorthop20164033
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of dynamic hip screw and proximal femoral nail for fracture of intertrochanteric femur

Abstract: <p class="abstract"><strong>Background:</strong> The aim of the present study was to compare the result in terms of rate of union, time of ambulation and functional recovery of fracture intertrochanteric femur treated by dynamic hip screw (DHS) and proximal femoral interlocking nail (PFN) and to compare complications in terms of implant failure, infection, blood loss and C arm exposure in both groups.</p><p class="abstract"><strong>Methods:</strong> This was a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…5 Yadav et al, in their study assessing 96 cases road traffic accidents constituted 50.8% of cases. 7 In our study average union time was 14.5 weeks, ranging from 10 weeks to 19 weeks. Gadegone et al in their study comprising 82 fractures average time for union was 14.2 weeks.…”
Section: Discussionmentioning
confidence: 52%
“…5 Yadav et al, in their study assessing 96 cases road traffic accidents constituted 50.8% of cases. 7 In our study average union time was 14.5 weeks, ranging from 10 weeks to 19 weeks. Gadegone et al in their study comprising 82 fractures average time for union was 14.2 weeks.…”
Section: Discussionmentioning
confidence: 52%
“… In study by Ravi Shankar et al, in 2015-showed PFN (91.7%) has good to excellent result compared to DHS (75%) [17] .  Jakkala et al in 2019 [18] , Chaitanya et al in 2015 [19] , Kumar R et al in 2012 [20] , Jose et al in 2017 [21] , Yadav et al in 2016 [22] , Mundla et al in 2017 [23] , Chowdhary et al in 2017 [24] , Jonnes et al in 2016 [25] , Nuber et al in 2003 [25] , Zhang et al in 2014 [27] , Avinash Kumar et al…”
Section: Resultsmentioning
confidence: 99%
“…The surgical management was primary treatment choice for intertrochanteric fractures. It is always aims to restore the anatomy and function without prolonged immobilization [2] . Surgical management with stable fixation allows early mobilization and reduces postoperative complications.…”
Section: Introductionmentioning
confidence: 99%